2009
DOI: 10.1002/iub.292
|View full text |Cite
|
Sign up to set email alerts
|

Search for the “ideal analgesic” in pain treatment by engineering the mu‐opioid receptor

Abstract: SummaryThe myriad of side effects that associate with morphine has been problematic in the clinical use to manage moderate to severe pain. It has been the holy grail of the pharmacologists to develop a compound, or treatment paradigm that could retain the analgesic effect of the drug as eliminating or reducing the side effects, mainly the tolerance and addiction development associates with chronic usage of the drug. In our earlier receptor structure/activities studies, we discovered an unique mutation of a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Opioids have long been used to treat severe pain 1 . However, long-term use leads to tolerance, dependence and addiction 2 . No currently available drugs can completely substitute for opioids in most clinical opioid indications, and no treatment paradigms can successfully prevent the development of tolerance and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids have long been used to treat severe pain 1 . However, long-term use leads to tolerance, dependence and addiction 2 . No currently available drugs can completely substitute for opioids in most clinical opioid indications, and no treatment paradigms can successfully prevent the development of tolerance and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that δ‐receptor agonists as well as δ‐receptor antagonists provide significant modulation of the pharmacological effects of μ‐agonists. It has been shown that agonists at the δ‐receptor can enhance the analgesic potency and efficacy of μ‐agonists while δ‐antagonists can prevent or diminish the development of tolerance and physical dependence by μ‐agonists; multiple and controversial interpretations of the observed phenomena have been made .…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been pursued to identify technologies that meet these characteristics. At the drug discovery level, attempts have been made to identify an ideal analgesic by engineering the mu‐opioid receptor (Tao et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been pursued to identify technologies that meet these characteristics. At the drug discovery level, attempts have been made to identify an ideal analgesic by engineering the mu-opioid receptor (Tao et al, 2010). Others have concentrated on ways to alter existing analgesics or to combine existing analgesic compounds with drugs that may improve effectiveness while minimizing adverse effects (Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%